Feasibility of home exercises to enhance the benefits of tango dancing in people with Parkinson's disease. (February 2019) - Albani, Giovanni; Veneziano, Giuseppe; Lunardon, Clara; Vinci, Calogero; Daniele, Alessandra; Cossa, Federico; Mauro, Alessandro
Highlights: Dance can provide relevant benefit in rehabilitation of Parkinsonian patients. Health improvement has been reported for PD people dancing tango. Extensive professional tango training may be difficult for Parkinsonian patients. A home based Tango training protocol was tested. After five weeks, ten patients ameliorated their UPDRS and kinematic performances. Abstract: Background: A style of dance called tango translates clinical practice into a new philosophy and rehabilitative approach for individuals with Parkinson's disease (PD). The style of dance mixes music, self-generated and external cued strategies and social and emotional recovery. In recent years, there has been an increase in the number of studies reporting health benefits for people diagnosed with PD who dance tango. However, there are some organisational limitations to people participating in dance classes, including having trained Tango teachers, an appropriate space for dancing, and schedule that allows for participants with motor inabilities. Methods: This pilot study involved the observation of PD patients who completed four days of home exercise plus a tango dance lesson each week for five weeks. Results: Ten PD patients improved their quality of life, their motor score on the Unified Parkinson's Disease Rating Scale and their kinematic performances. Conclusions: We propose a protocol of exercises that has been derived from the tango dance and that can be performed in a patient's home.